Welfare payments and crime - Foley, C. Fritz (Working paper series / National Bureau of Economic Research, 2008)
"This paper tests the hypothesis that the timing of welfare payments affects criminal activity. Analysis of daily reported incidents of major crimes in twelve U.S. cities reveals an increase in crime over the course of monthly welfare payment cycles. This increase reflects an increase in crimes that are likely to have a direct financial motivation like burglary, larceny-theft, motor vehicle theft, and robbery, as opposed to other kinds of crime like arson, assault, homicide, and rape. Temporal patterns in crime are observed in jurisdictions in which disbursements are focused at the beginning of monthly welfare payment cycles and not in jurisdictions in which disbursements are relatively more staggered"--National Bureau of Economic Research web site